Clenbuterol immunosensors based poly(3, 4-Ethylenedioxythiophene)/ multiwall carbon nanotube (PEDOT/MWCNT) hybrid composite - A.Talib, Nurul Ain; Syed Zainol Abidin, Siti Nurul Jannah; Salam, Faridah; Sulaiman, Yusran (Elsevier, 2016)
Electrochemical immunosensors based PEDOT/MWCNT hybrid composite for detection of clenbuterol antibiotic has been developed. It shows promising properties as biosensors platform with combination of high conductive properties of poly(3,4-ethylenedioxythiophene) (PEDOT) and high surface area of carbon nanotube (CNT). Based on cyclic voltammetry (CV) measurement in potassium ferricyanide (K3[Fe(CN)6]), lower peak potential separation (90.33 mV) and higher peak current (0.197 mA) were obtained compared with unmodified electrode (114.75 mV and 0.163 mA).This immunosensor, which was based on direct competitive method, was examined with standard clenbuterol hydrochloride for detection of clenbuterol through chronoamperometry at -0.1 V.